(untitled) (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2018)
The present survey is characterized by the attempt to make a de jure seasoned reconstruction that avoids the easy temptation to interpret in an overly extensive manner the jurisprudential practice, both internal and international, in favor of overcoming the rules on immunity, seen as a "hateful privilege" to be fought at any cost. Indeed, the recognition of the judicial exemption, protecting the State and the bodies acting on its behalf, has allowed, over time, the preservation of international relations and, ultimately, the same peaceful coexistence of the international community.